Role of the Carotid Bodies in the Hypertensive and Natriuretic Responses to NaCl Load in Conscious Rats - Silva, Elaine Fernanda da [UNESP]; Soares de Melo, Aryanne Batista; Lobo Junior, Eulicio de Oliveira; Rodrigues, Karla Lima; Naves, Lara Marques; Tomazelli Coltro, Wendell Karlos; Silva Rebelo, Ana Cristina; Freiria-Oliveira, Andre Henrique; Menani, Jose Vanderlei [UNESP]; Pedrino, Gustavo Rodrigues; Colombari, Eduardo [UNESP] (Frontiers Media Sa, 2018)
Hyperosmotic challenges trigger a hypertensive response and natriuresis mediated by central and peripheral sensors. Here, we evaluated the importance of the carotid bodies for the hypertensive and natriuretic responses to acute and sub-chronic NaCl load in conscious rats. Male Wistar rats (250-330 g) submitted to bilateral carotid body removal (CBX) or sham surgery were used. One day after the surgery, the changes in arterial blood pressure (n = 6-7/group) and renal sodium excretion (n = 10/group) to intravenous infusion of 3 M NaCl (1.8 mL/kg b.w. during 1 min) were evaluated in non-anesthetized rats. Another cohort of sham (n = 8) and CBX rats (n = 6) had access to 0.3 M NaCl as the only source of fluid to drink for 7 days while ingestion and renal excretion were monitored daily. The sodium balance was calculated as the difference between sodium infused/ingested and excreted. CBX reduced the hypertensive (8 +/- 2 mmHg, vs. sham rats: 19 +/- 2 mmHg; p < 0.05) and natriuretic responses (1.33 +/- 0.13 mmol/90 min, vs. sham: 1.81 +/- 0.11 mmol/90 min; p < 0.05) to acute intravenous infusion of 3 M NaCl, leading to an increase of sodium balance (0.38 +/- 0.11 mmol/90 min, vs. sham: -0.06 +/- 0.10 mmol/90 min; p <0.05). In CBX rats, sub-chronic NaCl load with 0.3 M NaCl to drink for 7 days increased sodium balance (18.13 +/- 4.45 mmol, vs. sham: 5.58 +/- 1.71 mmol; p <0.05) and plasma sodium concentration (164 +/- 5 mmol/L, vs. sham: 140 +/- 7 mmol/L; p 0.05), without changing arterial pressure (121 +/- 9 mmHg, vs. sham: 116 +/- 2 mmHg). These results suggest that carotid bodies are important for the maintenance of the hypertensive response to acute hypertonic challenges and for sodium excretion to both acute and chronic NaCl load.
Keywords: carotid afferents; blood pressure; sodium balance; hypernatremia; high salt intake; fluid-electrolyte control